بيع الغرر و صوره المعاصرة - عاد, شيماء; برة, سارة (جامعة الوادي - University of Eloued, 2019)
ىذه الدراسة ابؼوسومة ب )بيع الغرر وصوره ابؼعاصرة (, وكان الإشكال الرئيسي فيها ىو: ما ىو بيع الغرر, وماىي أبرز صوره ابؼعاصرة, وقد سعينا للإجابة عن ىذا الاشكال من خلال مبحثتُ: التعاريف ابؼتعلقة ببيع الغرر وحكمو وضوابطو )دراسة نظرية(, تطبيق بيع الغرر على الصور ابؼعاصرة )دراسة تطبيقية(. وقد توصلنا إلذ بصلة من النتائج لعل أهمها: بيع الغرر بكل صوره القديدة وابؼعاصرة منهي عنو, البيع الغرر صور ونماذج معاصرة كثتَة, ولكل صور الغرر ابؼعاصرة بدائل شرعية عوضا عن الصور الغتَ شرعية. Summary This study is related to the sale of gharar and its contemporary forms. The main problem was: What is the sale of gharar, and what is the most prominent contemporary image? And we have sought to answer these forms through two studies: Definitions concerning the sale of gharar and its ruling and its controls, Gharar on contemporary images (applied study(. We have reached a number of results, the most important of which are: selling gharar in all its old and contemporary forms is forbidden, selling gharar pictures and many contemporary models, and all contemporary Gharar pictures legitimate alternatives instead of illegal images
مذكرة ليسانس
Keywords: بيع الغرر/ الصور المعاصرة; Vente de gharar/images contemporaines